PRIORITY OF ROLE PLAYS IN TEACHING LANGUAGE FOR YOUNG LEARNERS - Niyazova Feruza Saydullayevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The study focused on the analysis and teaching of young learners with the help of game strategies and determined its goal – to improve the learner's vocabulary learning skills who have difficulties. Everyone knows that games are fun, but some people think that they are only fun. In fact, using games is an enjoyable way of achieving many educational objectives. They can be used to reinforce newly acquired information after it has been taught; they can be used to review the material even if it has been taught days, weeks, or even years ago.